Using molecular methods to diagnose, classify, and treat neonatal sepsis: a scoping review - Lee, Catherine Y.; Zven, Sidney E.; Sathya, Shreyas A.; Abukhalaf, Danielle; Sahoo, Sneha; Samal, Pratyusha; Prescott, Stephanie M. (Frontiers in Pediatrics, 2025)
IntroductionNeonatal sepsis is a dysregulated immune response to bloodstream infection causing serious disease and death. Our review seeks to integrate the knowledge gained from studies of multiple molecular methods- such as genomics, metabolomics, transcriptomics, and the gut microbiome- in the setting of neonatal sepsis that may improve the diagnosis, classification, and treatment of the disease. Sepsis claims over 200,000 lives annually worldwide and remains a top 10 cause of infant mortality in the US. Diagnosis and treatment of neonatal sepsis remains a challenge as its mechanisms are poorly understood.MethodsWe conducted a scoping review of literature published between 2018 and 2024. Of 1,043 articles screened, 30 were included in the final review.ResultsThe gut microbiome is associated with both pathogenicity and protection in the setting of neonatal sepsis, while expression levels of immune response and regulation help classify neonatal response to septic events. Metabolomic studies reveal possible biomarkers to detect, classify, and predict neonatal sepsis morbidity and mortality, and proteomic studies confirm mechanisms predicted by the other models.DiscussionStudies using molecular methods foster greater understanding of neonatal sepsis and show promise to improve diagnosis, classification, and therapeutic intervention. Future research using multi-omic analyses may further elucidate the development and progression of inflammatory processes that occur as sepsis progresses.